Integration of Pesantren Values in the Management of Madrasahs (A Study at MTs Ma'arif Cikedung Maja Majalengka) - Nurmaidah, Ade Syifani; Yani, Ahmad (The Future of Education Journal, 2025)
This research is motivated by the fact that Madrasah education in Indonesia cannot be separated from the influence of Islamic Boarding School values ​​which are integrated into it. Islamic boarding schools, which are the oldest Islamic educational institutions in Indonesia, play an active role in facilitating various components in formal educational institutions in Indonesia, especially Madrasas. Islamic boarding school values ​​can be integrated with Madrasah management and have an important role in various aspects that can influence the success of madrasah governance in achieving its goals as a formal educational institution in Indonesia, one of which is MTs Ma'arif Cikedung Maja Majalengka. This research aims to identify and assess the impact of Islamic Boarding School values ​​on Madrasah management at MTs Ma'arif Cikedung Maja Majalengka. The research method used in this research is a qualitative descriptive research method. The techniques used are interviews, observation and documentation. The results of this research show that Islamic boarding school values ​​in madrasa management at MTs Ma'arif Cikedung include the madrasa curriculum which integrates the teaching of morals, worship and independence.